Affect and cortisol mechanisms through which acute exercise attenuates cigarette cravings during a temporary quit attempt. (May 2018) - De Jesus, Stefanie; Prapavessis, Harry
Abstract: Introduction: A number of mechanisms have been proposed to explain how exercise attenuates cravings among temporarily abstinent smokers; however, research has presented mixed findings. The aim of this study was to further investigate the mechanistic role of positive and negative affect and cortisol in the exercise-craving reduction relationship. Methods: Adult smokers ( N  = 110, male = 56, M age = 33.1, M cigarettes/day = 15.4) provided baseline affective and cortisol data (T1). After an 18-h period of abstinence, participants were randomized to a passive sitting (PSG) or moderate exercise group (MEG; 40–68% of heart rate reserve) for 10 min. Affect and cortisol data were also collected immediately before (T2) and after (T3) the condition. Results: The smoking abstinence manipulation increased cravings ( p  < 0.001, eta = 0.40) and negative affect ( p  < 0.001, eta = 0.17), as well as decreased positive affect ( p  < 0.001, eta = 0.08) and cortisol (trending, p  = 0.07, η2 = 0.04). As expected, a significant reduction in cravings from T2 to T3 was found for MEG but not PSG ( p  < 0.001, eta = 0.25). Mediation was tested using Sobel and bootstrapping tests with residual change scores of mediators and cravings. Findings showed that both positive and negative affect, but not cortisol, mediated the relationship between exercise and cravings. Conclusions: Understanding the mechanisms by which exercise induces craving reductions will better allow researchers and healthcare professionals to infer causality and implement interventions guided by the processes that yield such desirable outcomes. Highlights: This is one of the largest RCTs conducted in this area thus far. Mediation was tested using a rigorous method. Positive and negative affect are involved in the exercise-craving reduction link. Cortisol was not found to be involved in the exercise-craving reduction relationship.